APLIKASI MOTIF MANUSKRIP PADA BATIK: Pewarisan Budaya melalui Proses Pembelajaran terhadap Mahasiswa ISI Padangpanjang - yanuarmi, dini (Studi Budaya Nusantara, 2020)
This paper describes the motives found in manuscripts or ancient manuscripts are tangible cultural heritage, which can be categorized as visual culture. Its presence can be seen in plain view and all the time. A noble and monumental cultural heritage, can be threatened by extinction due to human activities and natural disasters. It is fitting for the cultural heritage of the heritage of the past to be preserved and maintained. To maintain the sustainability of these motifs can be revitalized and applied to various media and techniques, such as batik. Batik in the form of one technique in decorating the fabric surface with the application of motifs found in the manuscript. More than that, the existing motives can be developed by creating without changing the original shape. The Craft Art Study Program at the Indonesian Art Institute in Padangpanjang after collaborating with the Regional Literature Study Program of Andalas University, tried to maintain the historical heritage by applying manuscript motifs to batik. The motive that has been applied is the manuscript motif found in the Pakandangan area of Padangpariaman district and Lunang Silaut in the South Coast district. Some works designed by students interested in textiles are made using natural and synthetic coloring. So that batik illumination is born that is creative, innovative and competitive.